2015
DOI: 10.1038/bjc.2015.418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori eradication on the development of metachronous gastric cancer after endoscopic treatment: analysis of molecular alterations by a randomised controlled trial

Abstract: Background:Whether Helicobacter pylori eradication actually suppresses the development of metachronous gastric cancer (MGC) after endoscopic resection (ER) remains controversial. The aims of this study were to clarify (1) the molecular markers related to carcinogenesis in intestinal metaplasia (IM) by a cross-sectional study, and (2) the changes of those markers by an open-label, randomised controlled trial (RCT) of H. pylori treatment.Methods:First, we evaluated microsatellite instability (MSI), the methylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 54 publications
2
64
0
Order By: Relevance
“…87 However, there have been few reports on the changes of MSI and CIN (loss of heterozygosity, LOH) after H. pylori therapy. Our own previous studies 32,45 were exceptions, but in those reports we investigated MSI and LOH only in patients with IM and not in the context of atrophy. These molecular alterations in IM did not change significantly after the eradication, even in patients who underwent ER for early GC.…”
Section: Effects Of H Pylori Eradication On Molecular Eventsmentioning
confidence: 88%
See 1 more Smart Citation
“…87 However, there have been few reports on the changes of MSI and CIN (loss of heterozygosity, LOH) after H. pylori therapy. Our own previous studies 32,45 were exceptions, but in those reports we investigated MSI and LOH only in patients with IM and not in the context of atrophy. These molecular alterations in IM did not change significantly after the eradication, even in patients who underwent ER for early GC.…”
Section: Effects Of H Pylori Eradication On Molecular Eventsmentioning
confidence: 88%
“…However, studies on the changes in the molecular phenotype in the background mucosa following H. pylori treatment in patients who have undergone ER for gastric neoplasms are limited. 31,32,38,41,45 Recently, the biomarkers for GC development after H. pylori eradication were discussed, and it was found that residual GC-related molecular events, even after H. pylori eradication, may be a surrogate marker of GC. 30,32,34,38,41,45,46 The CpG island methylator phenotype (CIMP), which is characterized by extensive hypermethylation of multiple CpG islands within the genome, is currently recognized as one of the major mechanisms in gastric carcinogenesis, 89 although there is no gold standard with respect to gene panels or the number of marker thresholds used to define CIMP.…”
Section: Effects Of H Pylori Eradication On Molecular Eventsmentioning
confidence: 99%
“…In addition to recurrence of and survival from the primary cancers, development of metachronous gastric cancers is an important issue, because the whole stomach is preserved after endoscopic resection. Although an RCT from Japan revealed H. pylori eradication after gastric endoscopic resection significantly reduced development of metachronous gastric cancers at the 3-year follow-up [41], it is still controversial whether H. pylori eradication would really reduce development of metachronous gastric cancers after gastric endoscopic resection from recent evidence [34,[42][43][44]. Further studies are necessary in this area, especially regarding appropriate prevention and surveillance of metachronous cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies regarding short-term and/or long-term outcomes in specific or general ESD patients were identified [31][32][33][34]. As the short-term outcomes in patients at high risk of thromboembolism who were regularly taking antiplatelet agents, Ono et al [31] reported a 26 % post-ESD ulcer bleeding rate, which led to early termination of the prospective cohort study.…”
Section: Therapeutic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation